2014
DOI: 10.3892/ijo.2014.2451
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ARHGDIA expression is associated with poor prognosis in HCC and promotes invasion and metastasis of HCC cells

Abstract: Abstract. Rho GTPases control a wide range of cellu lar processes and contribute to tumor invasion and metastasis. As a regulator of Rho activity, ARHGDIA is aberrantly expressed in several types of tumors and plays different roles in the tumor process. To elucidate the role of ARHGDIA in HCC, we investigated the patterns of its expression, prognosis and clinical profiles in HCC. Functional assays were performed to investigate whether the alteration of ARHGDIA has an effect on cell growth, migration and invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…These findings are in line with the previous report that EZH2 regulates actin polymerization in prostate cancer [34]. Loss of RhoGDIγ expression is associated with poor prognosis and promotes metastasis and invasion in hepatocellular carcinoma [35]. Our results indicate that EZH2 is a key arbiter mediating cell motility through RhoGDIγ.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in line with the previous report that EZH2 regulates actin polymerization in prostate cancer [34]. Loss of RhoGDIγ expression is associated with poor prognosis and promotes metastasis and invasion in hepatocellular carcinoma [35]. Our results indicate that EZH2 is a key arbiter mediating cell motility through RhoGDIγ.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the NF-kappa-B pathway, the JNK pathway is also a specific pathway in tumor initiation and progression, including PC [ 47 , 48 ]. A specific regulator of Rho protein exchange reactions which is crucial for JNK pathway, ARHGDIA (see row 2 of Table 1 , with betweenness 94 and permutation FDR 0.012), was also identified using our method and functions in several types of tumors [ 49 , 50 ]. In addition, this apoptosis inhibitory protein has been confirmed to control Rho protein homeostasis and participate in the initiation and progression of PC through the apoptosis associated GDP/GTP exchange reaction via RhoA-Rho pathway [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite having no binding to DNA directly, HBx can deregulate cellular gene expression by interacting with transcription regulators in the nucleus [24, 22]. Previous reports showed that full-length HBx can transcriptionally suppress a subset of important tumor-related genes through enhancing the promoters binding to transcription suppressors like E2F1, SMAD4, YY1 and MAZ [2325].…”
Section: Discussionmentioning
confidence: 99%